Exploring more sustainable routes to acrylate monomer manufacture - Schofield, Laura Jayne (2016)
Acrylic based monomers are used to create a wide range of organic polymers with applications from false nails to lighting panels and from lightweight, scratch-proof laptop screens to viewing windows in aquariums and submarines. Petrochemicals have been the predominant feedstock for these monomers since their introduction, but moves to make the industry “cleaner” and “greener” have led to a growing interest in renewable resources. Exploiting such resources for bulk plastic manufacture is the focus of this project.